REPRESENTASI CITRA DIRI PRIA DEWASA DALAM IKLAN “MEN’S BIORE” (VERSI COOL OIL CLEAR- RIDE ALONG) - Syarifah Elsa Ifnida (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Advertising at this time not only be function as a media for promotional activities, delivering messages about products, but further acts as the creator and shaper of reality. There are story that are built by the advertiser’s company, even the stories that are built are often embedded in minds of the public, because these advertisements are aired repeatedly and for a long time. The meaning that appears in advertisements is usually in the form of an impression that adds to the complex definition of a person’s self-image. The impression of self-image like this makes a person use product that are not needed as useful, but only funtion as an enhancer for the image of himself. Men’s Biore version of Cool Oil Clear Ride Along, in this advertisement, some ideal adult male figures who are masculine, adventurous, caring and paying attention to the appearence of facial hygiene that has been adjusted from the characteristics of it’s market segmentation. So that it will rise to an impression and self-image that causes the advertisement audience to think that if they want to be ideal adult male as in advertising,it can be fufilled by using the product as well. In the advertisement, it has presented a picture of adult male self-image that has been constructed according to the maerketing needs of a product. Keywords: Representation, Advertising, Male Self-image, Masculine Abstrak: Iklan pada masa ini tidak hanya berfungsi sebagai media aktivitas promosi, penyampai pesan tentang produk-produk, namun lebih jauh berperan sebagai pencipta dan pembentuk realitas.. Terdapat cerita yang dibangun oleh perusahaan pengiklan, bahkan cerita yang dibangun tersebut kerap melekat di pikiran khalayak, karena iklan tersebut di tayangkan secara berulang-ulang dan dalam jangka waktu yang lama. Makna yang muncul dalam iklan biasanya berupa kesan penggambaran yang menambah kompleks dari definisi citra diri seseorang. Kesan citra diri yang seperti ini membuat seseorang menggunakan produk-produk yang secara kegunaan tidak terlalu diperlukan, namun hanya berfungsi sebagai penambah kesan indah untuk citra dirinya. Salah satu iklan yang mengandung unsur citra diri dan maskulinitas yang dikemas dalam produk perawatan wajah untuk pria dewasa ialah iklan Men’s Biore versi Cool Oil Clear Ride Along. Pada iklan ini, beberapa sosok pria dewasa ideal di masa sekarang yang maskulin, memiliki jiwa petualang, peduli dan memperhatikan penampilan kebersihan wajah yang sudah disesuaikan dari karakteristik segmentasi pasarnya. Sehingga akan memunculkan suatu kesan dan citra diri yang menyebabkan penonton iklan berpikir bahwa jika hendak menjadi pria dewasa yang ideal seperti dalam iklan, bisa dipenuhi dengan memakai produk tersebut juga. Dalam iklan tersebut telah menampilkan gambaran citra diri pria dewasa yang sudah dikonstruksi sesuai kebutuhan marketing sebuah produk. Kata kunci : Representasi, Iklan, Citra diri Pria, Maskulin